2018
DOI: 10.1002/asl.844
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and geographical variability of nitryl chloride and its precursors in Northern Europe

Abstract: Measurements of nitryl chloride (ClNO2) and its precursors (O3, NO2, particulate chloride) were made in 2014–2016 at three contrasting locations in the United Kingdom: Leicester, Penlee Point and Weybourne. ClNO2 was observed at all sites and in every season, with the highest concentrations between 00:00 and 04:00 GMT. The median nocturnal concentration of ClNO2 ranged between the detection limit (4.2 ppt) and 139 ppt. A clear seasonal cycle, with maxima in spring and winter, and significant differences betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(52 citation statements)
references
References 61 publications
4
44
4
Order By: Relevance
“…The AMS concentrations (PM 1 ) were on average ≈ 1 % of those reported by the MARGA (TSP) with the correlation between them indicating that the AMS chloride (PM 1 ) is mainly due to sea salt rather than NH 4 Cl. If we assume that ≈ 10 % of the sea salt mass (TSP) is associated with the fine mode (PM 1 ) as previously derived (Sommariva et al, 2018), we can use the MARGA (TSP) [Cl − ] to estimate that the true PM 1 [Cl − ] would be about an order of magnitude higher than measured by the AMS. Under the assumption that this is true, f is > 0.67 in all seven regions, implying that a lack of Cl − is not the reason for low values of ε, as may be expected for a marine environment.…”
Section: Factors Influencing the Clno 2 Production Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…The AMS concentrations (PM 1 ) were on average ≈ 1 % of those reported by the MARGA (TSP) with the correlation between them indicating that the AMS chloride (PM 1 ) is mainly due to sea salt rather than NH 4 Cl. If we assume that ≈ 10 % of the sea salt mass (TSP) is associated with the fine mode (PM 1 ) as previously derived (Sommariva et al, 2018), we can use the MARGA (TSP) [Cl − ] to estimate that the true PM 1 [Cl − ] would be about an order of magnitude higher than measured by the AMS. Under the assumption that this is true, f is > 0.67 in all seven regions, implying that a lack of Cl − is not the reason for low values of ε, as may be expected for a marine environment.…”
Section: Factors Influencing the Clno 2 Production Efficiencymentioning
confidence: 99%
“…the Los Angeles Basin in California (Riedel et al, 2012a;Wagner et al, 2012;Young et al, 2012). Other studies included coastal sites in Canada (Osthoff et al, 2018) and coastal/urban sites in the United Kingdom (Bannan et al, 2015(Bannan et al, , 2017Priestley et al, 2018;Sommariva et al, 2018). Whereas ClNO 2 was initially believed to play a significant role only in areas with marine influence (Behnke et al, 1997;Keene et al, 1999), midcontinental measurements in the US (Thornton et al, 2010;Riedel et al, 2013;Faxon et al, 2015) revealed the im-portance of anthropogenic sources (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The discrepancy among previous studies and between those works and the present one is difficult to deduce and requires further investigation. Several possible causes could lead to different simulated levels of halogens and their impact on oxidants, including the different mechanisms of producing and recycling halogen species (Sarwar et al, 2019), spatial resolution (Sommariva et al, 2018), emission inventory (Wang Q. Li et al: Halogen impact on air quality in Europe Figure 3. Monthly average OH and HO 2 concentration in the BASE simulation and changes due to chlorine (CL) and full halogen chemistry (HAL).…”
Section: Influence Of Halogen Chemistry On the Atmospheric Oxidationmentioning
confidence: 99%
“…A number of modeling studies have been conducted to investigate the impact of individual halogen species on air quality. The chemistry of chlorine, mainly that of nitryl chloride (ClNO 2 ), has been reported to increase the oxidation capacity and the formation of O 3 in recent studies (Sarwar et al, 2012(Sarwar et al, , 2014Li et al, 2016;Sherwen et al, 2017;Sommariva et al, 2018). Bromine (Fernandez et al, 2014) and iodine (Saiz-Lopez et al, 2014) chemistry are reported to decrease the concentration of O 3 over oceanic and terrestrial regions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation